Aflatoxin B1 induced renal and cardiac damage in rats: Protective effect of lycopene - Yilmaz, Seval; Kaya, Emre; Karaca, Aysegul; Karatas, Ozhan (Elsevier Sci Ltd, 2018)
This study was conducted to investigate the protective effects of lycopene against the toxic effects of Aflatoxin B-1 (AFB(1)) exposure in kidney and heart of rat by evaluating antioxidant defense systems and lipid peroxidation (LPO). Forty-two healthy three-month-old male Wistar-Albino rats were used in this study. The animals were randomly divided into six experimental groups including 7 rats in each. These groups were arranged as follows: control group, lycopene (5 mg/kg/day, orally for 15 days) group, AFB(1) (0.5 mg/kg/day, orally for 7 days) group, AFB(1) (1.5 mg/kg/day, orally for 3 days) group, AFB(1)(0.5 mg/kg/day, orally for 7 days) + lycopene (5 mg/kg/ day, orally for 15 days) group and AFB(1) (1.5 mg/kg/day, orally for 3 days) + lycopene (5 mg/kg/day, orally for 15 days) group. The animals were sacrificed at the end of applications. In this study, malondialdehyde (MDA) levels significantly increased; while reduced glutathione (GSH), glutathione-S-transferase (GST), catalase (CAT), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and glucose-6-phosphate-dehydrogenase (G6PD) activities decreased in kidney and heart tissues. The significant reduction in the activities of antioxidant enzymes and non-enzymatic antioxidant system in AF treated rats as compared to the control group could be responsible for increased MDA levels observed during AF induced kidney and heart damage. The results showed increased urea, creatinine levels, as well as reduction sodium concentrations in plasma of AFB(1 )treated rats. There was lycopene showed protection against AF induced nephrotoxicity and cardiotoxicity.
Keywords: Aflatoxin; Malondialdehyde; Antioxidant; Kidney; Heart; Lycopene